2022
DOI: 10.3390/nu14122516
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Biscuits Enriched with Plant-Based Protein Contribute to Weight Loss and Beneficial Metabolic Effects in Subjects with Overweight/Obesity

Abstract: The present study aimed to assess the impact of daily consumption of a snack fortified with plant proteins with high content in amino acids with appetite regulating properties (BCAAs and L-arginine), as part of a dietary intervention, on weight loss. Seventy adults without diabetes (26 male, 44 female) and with overweight/obesity participated in a 12-week restricted dietary intervention and were randomized to either a control or an intervention group, consuming daily 70 g of conventional wheat biscuits (CB) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…It has to be reported that ArgB was further examined in a long-term study conducted in subjects with overweight/obesity following a hypocaloric diet. The results showed that participants who consumed the ArgB exerted significantly higher body weight reduction and lower energy intake compared to the participants who consumed isocaloric amounts of the control wheat biscuit [ 51 ]. Animal studies have shown that L-arg has a delayed and sustainable anorectic effect [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has to be reported that ArgB was further examined in a long-term study conducted in subjects with overweight/obesity following a hypocaloric diet. The results showed that participants who consumed the ArgB exerted significantly higher body weight reduction and lower energy intake compared to the participants who consumed isocaloric amounts of the control wheat biscuit [ 51 ]. Animal studies have shown that L-arg has a delayed and sustainable anorectic effect [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff of protein intake was 15 En%, so our results suggest that higher than 15 En% from protein may decrease fat mass. The previous study found that the group with the protein-added biscuits lost significantly more body weight and fat mass than the control group [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study did not determine a more precise dietary protein level needed for weight reduction. However, the e cacy of increased protein to support weight loss does have support from a human trial that used biscuits enriched with plant-based protein and found that the group with the protein-added biscuits lost signi cantly more body weight and fat mass than the control group [39].…”
Section: Discussionmentioning
confidence: 99%